Association between serum γ-glutamyl transferase and advanced colorectal adenoma among inpatients: a case-control study - Wang, Huijie; Zheng, Huanwei; Cao, Xu; Meng, Ping; Liu, Jinli; Zuo, Haiying; Zhang, Teng; Wang, Zhichao (Frontiers in Oncology, 2024)
Emerging evidence suggests a link between γ-glutamyl transpeptidase (GGT) and various malignancies. However, the relationship between GGT and advanced colorectal adenoma, a critical precursor to colorectal cancer, remains unclear. This study aimed to elucidate this relationship. We conducted a single-center retrospective study from April 2015 to June 2022, enrolling 3534 inpatients including 525 cases and 3009 controls. Data were extracted from the electronic medical records, encompassing clinicodemographic characteristics, co-morbidities, and several blood biochemical indicators. Utilizing logistic regression and curve fitting, we explored the relationship between GGT and advanced colorectal adenoma. After adjustment for confounding factors, we found that for each 20-unit increase in GGT, the risk of advanced colorectal adenoma increased by 6% (OR= 1.06 [1.01-1.12]). Moreover, individuals with high GGT levels (≥50 U/L) had a 61% higher risk of advanced colorectal adenoma compared to those with low GGT levels (<50 U/L) (OR=1. 61 [1.13-2.31]). Subgroup analysis demonstrated the robustness of these findings across subjects with different characteristics. High GGT levels were associated with higher odds of advanced colorectal adenoma. Our findings suggest that elevated GGT levels may serve as a potential diagnostic marker for advanced colorectal adenoma, providing new insights into its screening strategies.